1999
DOI: 10.1007/s001200050318
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral stent placement in hydronephrosis during pregnancy

Abstract: In this study we describe 22 cases of retrograde ureteral stent placement in pregnant women with therapy-resistant flank pain due to hydronephrosis. Eleven were primiparous and one patient expected twins. Eight of 22 patients presented symptoms of pyelonephritis. In 21 cases the hydronephrosis was located on the right and in 4 cases it was bilateral. Maximal lower calix diameter was 12 mm (range 9-22 mm). With the exception of two cases, sonographically controlled stent placement was performed under local anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It was reported that JJ ureteric stenting can be difficult in the third trimester due to the tortuosity of the ureter [13] . However, others did not confirm this [9–12,14–16] . All patients in our series had successful stenting.…”
Section: Discussionmentioning
confidence: 89%
“…It was reported that JJ ureteric stenting can be difficult in the third trimester due to the tortuosity of the ureter [13] . However, others did not confirm this [9–12,14–16] . All patients in our series had successful stenting.…”
Section: Discussionmentioning
confidence: 89%
“…They concluded that internal drainage should be well evaluated in complicated pregnancy hydronephrosis (20). Several studies have shown that DJS is an effective and safe method for symptomatic pregnancy hydronephrosis treatment (6,7,21,22). However, most of these studies are small case-group and noncomparative studies.…”
Section: Discussionmentioning
confidence: 99%
“…If there is no amelioration of symptoms despite a conservative approach, interventional treatments such as ureteral catheterization and percutaneous nephrostomy (PCN) may be required. Both PCN and double J stenting (DJS) are widely used methods to alleviate hydronephrosis in pregnancy (6,7). Symptomatic hydronephrosis is a urological emergency as it may cause premature labor and should be alleviated as quickly as possible.…”
Section: Introductionmentioning
confidence: 99%
“…4 When symptoms of urolithiasis in a pregnant patient are refractory to conservative treatments, such as analgesics, or if the patient becomes complicated by infection or acute renal failure or when symptomatic or severe hydronephrosis occur, temporizing measures such as ureteral stent or PCN are frequently used. 5,6 Intracardiac migration of ureteral double-J stent: A case report and review case repOrt led to an increase in potential complications from minor clinical symptoms, such as frequency, dysuria or mild intermittent hematuria to more severe problems, such as stent slipping, upward migration, fragmentation, encrustation, stone formation, subsequent ureteral obstruction, infection, unresolved hydronephrosis and ureteral fistula. 3 Migration into the renal pelvis ranges from 0.6 to 8.2%).…”
Section: Discussionmentioning
confidence: 99%